Early Stunting Education (PENTINGJADI) for Adolescents in RW 07 Pasa Lalang Kuranji in 2023: Pendidikan Stunting Sejak Dini (PENTINGJADI) pada Remaja di RW 07 Pasa Lalang Kuranji tahun 2023 - Dian Febrida Sari; Eka Putri Primasari; Widya Lestari; Farida Ariyani; Eza Yusnella; Mayyang S. Rifa; Maita Alifa; Natasha Angle; Jannatul Utami; Nurlaili (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
Teenagers are a group of people who need special attention, both physically and psychologically. Teenagers as the next generation must also be prepared to become a quality generation. To create a quality generation, teenagers can be trained as implementers of stunting prevention. Stunting is a chronic nutritional problem and is a condition of malnutrition that is related to nutritional deficiencies in the past. The impact of stunting that endangers the nation's future is the low quality of adolescent health. Stunting prevention can be done in the life cycle at the adolescent stage. Knowledge of adolescent nutrition, especially young women, regarding stunting is very important to prevent stunting. Providing education about stunting should start from adolescence in preparation for entering the preconception period. Therefore, direct involvement of teenagers in preventing stunting should be carried out by the teenagers themselves. Health workers, in this case, play a role in providing education to teenagers who will become future mothers and fathers in the future. Through the education provided, it is hoped that it can increase teenagers' knowledge about stunting, so that when the baby is born, the mother can provide appropriate nutrition to the child, so that the child avoids the problem of stunting.